2020
DOI: 10.21203/rs.3.rs-79499/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

System Dynamics Modeling of Health Workforce Planning to Address Future Challenges of Thailand’s Universal Health Coverage

Abstract: Background: System dynamics modeling can inform policy decisions of healthcare reforms under Thailand’s Universal Health Coverage. We report on this thinking approach to Thailand’s strategic health workforce planning for the next 20 years.Methods: A series of group model building sessions involving 110 participants from multi-sectors of Thailand’s health systems was conducted in 2017 and 2018. Policymakers, healthcare administrators, and practitioners were facilitated to co-create a causal loop diagram represe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Following the publication of the original article [ 1 ], an error was identified in the Conclusions of the Abstract section.…”
Section: Correction To: Hum Resour Health (2021) 19:31 Https://doiorg/101186/s12960-021-00572-5mentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], an error was identified in the Conclusions of the Abstract section.…”
Section: Correction To: Hum Resour Health (2021) 19:31 Https://doiorg/101186/s12960-021-00572-5mentioning
confidence: 99%
“…Thus, the bottom line is not just implementing or not implementing the lockdown, but it is, if the lockdown is to be implemented, how the Thai Government maintains the national economy (or at least minimizes the economic damage). A recent study from Israel suggests that a cyclical lockdown strategy (four days of complete lockdown alternating with ten days of reopening) was effective at halting the epidemic while limiting the negative effects on the economy [ 19 ]. However, such a proposal might not be practical in reality, as it significantly disrupted the working life of most people.…”
Section: Discussionmentioning
confidence: 99%
“…The official announcement to the public suggested that the lockdown policy was likely to be in effect for about 30–60 days. During the first wave of COVID-19 in Thailand, in early 2020, Leerapan et al estimated that the lockdown helped reduce the reproduction number by about 20% [ 19 ]. We postulated that the effect of the lockdown measure might vary between 20 and 60% as, this time, there were many more additional measures compared with the first wave, such as mass COVID-19 vaccination campaigns and active community screening.…”
Section: Methodsmentioning
confidence: 99%